Disaster event-based spring frost damage identification indicator for tea plants and its applications over the region north of the Yangtze River, China. (February 2023) - Tang, Junxian; Wang, Peijuan; Li, Xin; Yang, Jianying; Wu, Dingrong; Ma, Yuping; Li, Shirui; Jin, Zhifeng; Huo, Zhiguo
Highlights: Daily minimum air temperatures ( T min ) performs well in identifying spring frost events. ROC curve and Youden Index were used to determine the critical temperature threshold. The critical T min threshold triggering spring frost damage to tea plants in NYR was 3.7 °C. Two application cases revealed the T min threshold of 3.7 °C was acknowledged. Abstract: Spring frost damage (SFD) is the main meteorological disaster limiting the tea industry in the region of the north of the Yangtze River (NYR) in China. Research regarding an SFD indicator for tea plants is of great significance for prevention and control of spring frosts, as well as for timely monitoring and early warning. Based on daily minimum air temperatures ( T min ) and spring frost disaster records in NYR from 1961 to 2020, the Receiver Operating Characteristic curve (ROC) was used to evaluate the accuracy of frost identification, and the critical temperature threshold for SFD to tea plants was determined by jointly comparing Overall Accuracy and the Youden Index. The results showed that the area under the ROC curve was 0.977, indicating that T min performed well in identifying frost events. The critical temperature threshold for spring frost in NYR was determined as T min of 3.7 °C, and 93 % of frost occurrences were correctly identified. Based on the determined critical threshold of SFD, the number of spring frost days, first frost date (FFD), and last frost date (LFD) in NYR from 1961 to 2020 were analyzed. The results showed that the number of spring frost days in NYR decreased from north to south. FFD appeared earlier and LFD ended later in northern NYR than in southern NYR. These results provide theoretical and technical support for the monitoring and evaluation of spring frosts in NYR, and also for implementing SFD prevention and control measurements for tea plants by use of a critical temperature threshold.